2021
DOI: 10.1186/s13068-020-01869-8
|View full text |Cite|
|
Sign up to set email alerts
|

Combined whole cell wall analysis and streamlined in silico carbohydrate-active enzyme discovery to improve biocatalytic conversion of agricultural crop residues

Abstract: The production of biofuels as an efficient source of renewable energy has received considerable attention due to increasing energy demands and regulatory incentives to reduce greenhouse gas emissions. Second-generation biofuel feedstocks, including agricultural crop residues generated on-farm during annual harvests, are abundant, inexpensive, and sustainable. Unlike first-generation feedstocks, which are enriched in easily fermentable carbohydrates, crop residue cell walls are highly resistant to saccharificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 237 publications
(317 reference statements)
0
14
0
Order By: Relevance
“…The degradation of biomass containing recalcitrant polysaccharides is important in biofuel processing, for example, and the discovery of efficient CAZymes using ''omics''-based functional prediction in non-model organisms could help to optimize this process in the future. 41…”
Section: Are Chitin-related Factors Involved In Contacting Algal Surf...mentioning
confidence: 99%
“…The degradation of biomass containing recalcitrant polysaccharides is important in biofuel processing, for example, and the discovery of efficient CAZymes using ''omics''-based functional prediction in non-model organisms could help to optimize this process in the future. 41…”
Section: Are Chitin-related Factors Involved In Contacting Algal Surf...mentioning
confidence: 99%
“…The status of pectin could also influence the porosity and integrity of the cell wall [ 38 , 39 ]. The pectin main chain with can be highly methylated will need the additional enzymes for thorough breakdown, and, therefore, decrease the availability of substrates targeted by other pathogenic cell wall-degrading enzymes (CWDEs), such as hemicellulases and cellulases [ 40 ]. Previous studies on some crops (tomato, cotton and wheat) have suggested that a high degree of esterification (DE) level of pectin is positively correlated with plant defense.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to pectin, mAb BS-400-2 (recognizes callose), which did not show zero on heatmap, however, shows its association with other pectin recognizing mAbs in the PCA plot. Callose has been well documented in many studies for its roles in plant/microbial interactions; it has been found to be deposited around the infection sites to block the pathogens [ 15 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Different glycomic methods are required to study unique structural features of carbohydrates, such as linkage, monosaccharide content, or dp, and selecting the appropriate preparative and analytical method needs to be carefully considered (Tingley et al, 2021). Dietary polysaccharide analysis begins with hot water extraction from source material, followed by sequential fractionation by preparative column chromatography, solvent extraction, and ethanol precipitation.…”
Section: Current Glycomics Methods To Study Food Carbohydratesmentioning
confidence: 99%